STUDI KELAYAKAN USAHA PENANGKAPAN IKAN SECARA TRADISIONAL DI WILAYAH PESISIR KOTA MATARAM - MARINI, IDA AYU KETUT; ARTIKA, IDA BAGUS EKA (Ganec Swara, 2025)
Regarding efforts to increase the standard of living and income of fishermen, fishing business actors have the aim and desire to make a profit from each catch so that they can fulfill their family’s needs in addition to preparing for the next fish catch. Different conditions occur in the coastal areas of Mataram City, fishermen are still carrying out activities fishing using traditional methods without making modifications. Based on this, researchers are interested in researching the feasibility of traditional fishing carried out by fishermen on the coast of Mataram City. The author can explain the problem in this research, namely whether traditional fishing is still feasible for fishermen on the coast of Mataram City when viewed from the investment criteria of Net Present Value (NPV), Pay Back Period (PP), Profitability Index (PI) and Gross B /C. This type of research is research using a survey sample method with a sample size of 40 people. Based on the analysis of Net Present Value (NPV) investment criteria, a value of IDR is obtained. 34,451,030,-. Payback Period (PP) is 2 years 5 months 6 days, Profitability Index (PI) is 3.020 and Gross B/C is 1.48. It can be concluded that fishing activities carried out by coastal fishermen in Mataram City are still feasible.